A new DSI-SLM method for PAPR reduction in OFDM systems - Mohammady, Somayeh; Mohd Sidek, Roslina; Varahram, Pooria; Hamidon, Mohd Nizar; Sulaiman, Nasri (IEEE, 2011)
High PAPR is the main drawback of OFDM systems. DSI method and SLM method are two of the most promising techniques to reduce PAPR.